2015
DOI: 10.1097/md.0000000000001585
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Associated With an Increased Risk of Deep Vein Thrombosis

Abstract: The association between the hepatitis C virus (HCV) infection and the risk of myocardial infarction (MI) and stroke has been previously investigated. However, the association between the HCV infection and the risk of venous thromboembolism (VTE) has not been extensively discussed.Using the Longitudinal Health Insurance Database 2000 (LHID2000), we selected 3686 patients with newly diagnosed HCV infection. We randomly selected 14,744 people with no HCV or hepatitis B virus (HBV) infection as comparison group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 44 publications
1
34
1
1
Order By: Relevance
“…From a safety perspective, we observed a good clinical and biological tolerance for all patients. The two thrombo-embolic events reported by Vionnet et al might be related with the higher risk of thrombosis associated with the HCV infection [7]. Recently, our results were confirmed by others, who reported a very high efficacy and good tolerability of SOF 400 mg QD in hemodialysis or severe CKD patients [8,9].…”
supporting
confidence: 82%
“…From a safety perspective, we observed a good clinical and biological tolerance for all patients. The two thrombo-embolic events reported by Vionnet et al might be related with the higher risk of thrombosis associated with the HCV infection [7]. Recently, our results were confirmed by others, who reported a very high efficacy and good tolerability of SOF 400 mg QD in hemodialysis or severe CKD patients [8,9].…”
supporting
confidence: 82%
“…The International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) code was used for coding the diseases of interest in the present study. 29 , 30 To prevent medical fraud with overbilling for healthcare or inappropriate charges based on unconfirmed diagnoses, NHI sets strict rules on disease coding and regularly monitors coding and claims submitted for reimbursement by all participants of NHI beneficiaries. NHIRD provides reliable information for the proposed studies to explore the risk of VTE development in patients with gout.…”
Section: Methodsmentioning
confidence: 99%
“…117 No. 12/2017 tuberculosis21 and hepatitis C virus infection22 compared with controls (►Table 3). Two studies only recorded VTE incidence, and both showed significantly higher rates in patients with dermatomyositis (HR: 11.1; 95% CI: 5.2, 23.6) and liver cirrhosis (HR: 7.7; 95% CI: 5.2, 11.4) 23 compared with controls.…”
mentioning
confidence: 99%